Lies Behind Bars: An Analysis of the Problematic Reliance on Jailhouse Informant Testimony in the Criminal Justice System and a Texas-Sized Attempt to Address the Issue - Luke G. Allen (Washington University Law Review, 2020)
The advent of DNA technology in the late 1980s led to a wave of exonerations in the United States, shedding light on major problems with the U.S. criminal justice system. Many of these wrongful convictions were traced back to criminal informants, colloquially referred to as “snitches,” who provided incriminating testimony in exchange for a sentence reduction, leniency, inmate privileges, or some other perk. The correlation between wrongful convictions and informant testimony is a cause for concern, especially in Texas, where more people have been executed and exonerated than anywhere else in the country. This Note analyzes the use of criminal informants with a particular focus on jailhouse informants—inmates that come forward with the “confessions” of fellow inmates. First, this Note discusses the broad use of criminal informants throughout history and the problems that have arisen therefrom. Second, it examines Nolley v. State, the Texas Court of Criminal Appeals case that inspired legislative change in Texas. Third, this Note assesses Texas House Bill 34, which is Texas’s latest legislative effort to regulate the use of jailhouse informants. Finally, this Note proposes a solution to address the problem of unreliable jailhouse informant testimony that requires judges to serve a “gatekeeping role” through which they could filter out unreliable testimony before trial. As part of this solution, this Note recommends giving judges and defense attorneys access to a statewide database containing information on every jailhouse informant ever used so that they do not have to rely on the prosecution to produce that information. Though this solution will add to the workload of judges, it is necessary to prevent prosecutorial misconduct and ensure the integrity of the U.S. criminal justice system.
Keywords: Criminal law; Jailhouse informants; Nolley v. State No. 02-98-00253-CR (Tex. App. Fort Worth Sept. 23 1999); Texas House Bill 34; Exonerations; Wrongful convictions; Criminal informants